LOVE, SURVEILLANCE AND VIOLENCE IN RAFIKI (2018): A LESBIAN FEMINIST READING - Nolli, Carla Fernanda; Fistarol, Caique Fernando da Silva (Seven Editora, 2026)
This article examines how Rafiki (2018) articulates love, surveillance and violence in its representation of lesbian experience. Drawing on a lesbian feminist reading of Wanuri Kahiu’s film, inspired by Monica Arac de Nyeko’s short story “Jambula Tree,” the study argues that the film constructs the bond between Kena and Ziki as a force of mutual recognition while exposing the familial, social, and institutional mechanisms mobilized to discipline dissident desire. Methodologically, the discussion focuses on two sequences, read through the concepts of compulsory heterosexuality, heteronormativity, intersectionality, and lesbophobia in dialogue with formal elements of film language such as framing, lighting, color, and point of view. The analysis shows that Rafiki juxtaposes scenes of reciprocity, chromatic warmth, and affective openness with scenes of public exposure, humiliation, and coercion, thereby revealing that violence against lesbian women operates in both physical and symbolic registers. The article concludes that the film performs an aesthetically and politically significant intervention by affirming the legitimacy of desire between women and by making visible the social costs imposed on its existence.